Protection of hepatic cell damage and antimicrobial evaluation of chitosan-catechin conjugate - Cho, Young-Sook; Lee, Dae-Sung; Kim, Young-Mog; Ahn, Chang-Bum; Kim, Do-Hyung; Jung, Won-Kyo; Je, Jae-Young (Applied biological chemistry, 2013)
The chitosan-catechin conjugate was developed by free radical-induced conjugating reaction, and its protection ability against hydrogen peroxide-induced hepatic damage in human normal Chang liver cells and antimicrobial activity against methicillin-resistant Staphylococcus aureus (MRSA) and foodborne pathogens were investigated. Treatment of hydrogen peroxide (650 μM) on Chang liver cells decreased cell viability up to 59.38% compared to the non-treatment group; however, cotreatment of the chitosan-catechin conjugate increased cell viability up to 76.90% at 200 μg/mL, and the protection ability was significantly higher than the unmodified chitosan ( p <0.05). The chitosan-catechin conjugate significantly ( p <0.05) inhibited the formation of intracellular reactive oxygen species and lipid peroxidation in Chang liver cells. Moreover, the chitosan-catechin conjugate increased glutathione levels in normal condition as well as under oxidative stress by hydrogen peroxide. Additionally, the chitosan-catechin conjugate showed increased antimicrobial activity against MRSA and foodborne pathogens as compared to those of the unmodified chitosan.